Pemanfaatan Sari Belimbing Wuluh (Averrhoa bilimbi L.) pada Pemeliharaan Udang Vaname (Litopenaeus vannamei) untuk Menekan Populasi Bakteri Vibrio sp. Koloni Hijau - Handayani, Sri; Dwinanti, Sefti Heza; Hadi, Purnomo (Masyarakat Akuakultur Indonesia, 2019)
Sri Handayani, Sefti Heza Dwinanti and Purnomo Hadi. 2020. Utilization of Carambola Sari (Averrhoa bilimbi L.) in the Maintenance of Vaname Shrimp (Litopenaeus vannamei) to Suppress Population of Vibrio sp. Green Colony. Jurnal Sains Teknologi Akuakultur, 3(1) : 33-41. This research was conducted in July-August 2018 at PT. SyAqua Indonesia Serang, Banten. It used Completely Randomized Design (CRD) with three replicates and three treatments which were bilimbi juice in 20 ppm (T1), 30 ppm (T2) and without bilimbi or control (CT). The monitoring of Vibrio sp., defined as total Vibrio sp., totalÂ Â yellow colony, total green colony, the ratio of total green colony, survival rate of shrimp and water quality. The result showed that bilimbi juice was able to suppress the population of Vibrio sp. in the maintenance media and shrimp body. At the end of the maintenance period (d7-d9), total population of green colony in treatment were lower than control with the ratio of the green colony was 0%. In contrast, bilimbi juice with concentration 20 ppm and 30 ppm had no significant effect (P>0,1). The best survival rate was given by T2 about 16% and based on regression y = 0.3589x+5.0279 the optimal dose to protect shrimp from Vibrio sp. by using bilimbi juice is about 264,62 ppm.